The Influence of Principal Leadership and School Committees on Teacher Discipline - Putri Susanti, Gusma; Ma’as, Isyuliardi; Wandra, Novera; Bismark, O.P. (Strata Business Review, 2024)
This study examines the impact of the principal's leadership and the school committee on teacher disciplinary measures at UPT SDN 15 Sungai Padi, Sangir District, South Solok Regency. This research addresses the issue of leadership within the principal and school committee in relation to teacher discipline at UPT SDN 15 Sungai Padi. The population and sample for this study consisted of teachers and students from UPT SDN 15 Sungai Padi, totaling 65 individuals. The objective of this research is to (1) describe the leadership qualities of the principal, school committee, and teacher discipline at UPT SDN 15 Sungai Padi, (2) assess the impact of the principal's leadership on teacher discipline at UPT SDN 15 Sungai Padi, (3) evaluate the influence of the school committee on teacher discipline at UPT SDN 15 Sungai Padi, and (4) determine the combined influence of the principal's leadership and the school committee on teacher discipline at UPT SDN 15 Sungai Padi. This study employs a causal descriptive methodology. The data analysis employed multiple linear regression using the SPSS for Windows 27 software. The findings indicated that the principal's leadership exerted a substantial influence on teacher discipline, whereas the school committee had no noteworthy impact on teacher discipline. Furthermore, the combined effect of the principal's leadership and the school committee was found to have a significant impact on teacher discipline.